Ultrasound activated nanosensitizers for sonodynamic therapy and theranostics. (23rd February 2021) - Li, Lei; Lin, Huirong; Li, Dengfeng; Zeng, Yun; Liu, Gang
Abstract: Sonodynamic therapy (SDT) is a promising non-invasive therapeutic modality with an extensive application prospect. Due to the engineerable nature of nanotechnology, nanosensitizers with predominant advantages of increased SDT efficacy and targeting specificity have attracted more and more research recently. In this review, we introduce the current investigations of nanosonosensitizers and focus on the potential strategies on nanoparticles-assisted sonosensitizers to enhance SDT efficacy. We extensively discuss the biomedical applications of ultrasound activated nanosonosensitizers in SDT and theranostics.